Prevalence and antibiotic resistance of Campylobacter spp. in poultry and raw meat in the Can Tho Province, Vietnam - Schwan, Petter (2010)
The aims of the study were to investigate the prevalence and antibiotic resistance of Campylobacter jejuni and Campylobacter coli in chicken and chicken products, and to investigate farmer awareness of antibiotic resistance development. The study was conducted in the Can Tho province in Vietnam during six weeks in October to November 2008. Ninety-six samples from raw chickens were collected from twelve market places and analysed for the presence of Campylobacter. A total of 96 cloacal swabs from 20 farms were obtained and analysed for the presence of Campylobacter. Farmers were asked to answer eight questions concerning the housing of the chickens, modes of handling sick animals as well as use and knowledge of antibiotics and resistance development to antibiotics. None of the market samples were positive for Campylobacter spp. most likely due to faulty handling of samples, wrong sample selection and contaminant bacterial overgrowth. Seventy-six percent of the individual farm samples were positive for Campylobacter spp. (73/96), and 95% (19/20) of the farms had at least one positive sample. From the 73 positive samples, 28 isolates were chosen for further analysis, species identification and antibiotic resistance testing. Twenty-one percent of the isolates (6/28) were C. coli and 79% (22/28) were C. jejuni. Resistance was found to all examined antibiotics: erythromycin 7%, ciprofloxacin 71%, tetracycline 71%, streptomycin 21%, gentamicin 7% and nalidixic acid 71%. Campylobacter coli had an overall higher level of resistance than C. jejuni. Antibiotics were used in most farms and often in a profylactic manner. Most farmers chose substance depending on availability and cost and/or what the local salesperson recommended rather than consulting a veterinarian. Knowledge of resistance to antibiotics was generally low.